Preservation of Balinese batik knowledge as an effort to preserve indigenous knowledge - Igiriza, Miftahunnisa'; Valentino, Rahmat Alifin; Wiradharma, Gunawan; Fadhli, Rahmat; Adamy, Zulham; Anjani, Afifah (Universitas Padjadjaran, 2024)
Balinese batik, a traditional cloth, is rich in motifs and philosophical meanings that reflect the culture of the Balinese people and need to be preserved. Preservation efforts aim to ensure that the knowledge contained in Balinese batik can be sustainable in the long term. This study examined the knowledge and preservation of Balinese batik cloth to preserve indigenous knowledge. This study used a qualitative method by analyzing the knowledge contained in Balinese batik cloth using Peirce's semiotic approach and a case study to explore the preservation efforts carried out by the UPTD Bali Museum. The data collection technique used interview and observation methods, which were conducted from May to June 2024. Data analysis was carried out through data reduction, data presentation (data display), and conclusion. Study results showed that if examined more deeply, Balinese batik contained philosophical meanings that reflected the culture of Balinese society due to the influence of Hinduism and local values. Balinese batik motifs were also inseparable from the influence of Chinese cultural elements that contain spiritual and mythological values. The Bali Museum conducted preservation efforts through processes such as identifying and validating knowledge in local communities and academic circles, recording and storing this knowledge in a database, and disseminating it to the broader community. This study concludes that Peirce's semiotics can assist in identifying the indigenous knowledge of Balinese batik, and in this case, the Bali Museum plays an important role in preserving local wisdom.